Poetics of Resistance - Prica, Ines; Čale-Feldman, Lada; Senjković-Svrčić, Reana (1992)
The authoresses reflect on the multiple manifestations of war symbolism in Croatia 1991-92, considering it as an expression of the cultural resistance.
Projekt MZOS
ENG